Pengaruh Peran Budaya Organisasi Efektivitas Kepemimpinan dan Motivasi Kerja Pegawai Terhadap Kebijakan Badan Layanan Umum - Azis Ritonga (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2018)
Employee Motivation Against Public Service Agency PolicyThe background of this research is the change of status of Health Polytechnics of Surakarta from Civil Servant purely become Public Service Agency. Where in this form change make Health Polytechnics of Surakarta prepare their own budget. Thus there must be a change of management to address it. For that researchers are very interested to see the effect of Organizational Culture Roles, Leadership Effectiveness And Employee Motivation Against Public Service Agency Policy. The population in this research is all employees of Health Polytechnics of Surakarta. This research uses Simple random sampling which is a randomly chosen sampling technique. Statistical analysis using structural equation model (SEM). With 95% confidence level of research results showed that there is no significant positive relationship between organizational culture and leadership in Health Polytechnics of Surakarta.There is no significant correlation between organizational culture on policy of Health Polytechnics of Surakarta Public Service Agency (BLU).There is no significant correlation between work motivation toward leadership in Health Polytechnics of Surakarta.There is no significant correlation between work motivation to BLU policy in Health Polytechnics of Surakarta.There is no significant positive correlation between leadership of BLU policy in Health Polytechnics of Surakarta.